Are Adequate Vitamin D Levels Helpful in Fighting COVID-19? A Look at the Evidence - Hoong, Caroline Wei Shan; Huilin, Koh; Cho, Sanda; Aravamudan, Veeraraghavan Meyyur; Lin, Jaime Hui Xian (Hormone and Metabolic Research, 2020)
COVID-19 is a global pandemic with high mortality in vulnerable groups. Given the current lack of definitive treatment or vaccine that significantly reduces mortality rate, governments, researchers and healthcare providers are racing to find possible solutions to the crisis. Vitamin D and its analogues have been previously studied for their non-skeletal benefits. In particular, questions regarding their role in the modulation of immunity have re-surfaced, in view of possible epidemiological links observed between COVID-19 and vitamin D levels in selected populations. In this review, we highlight potential mechanisms and summarise the evidence for and against the potential role of vitamin D supplementation in our fight against COVID-19.
Keywords: vitamin D; bone/calcium homeostasis; COVID-19; SARS-CoV-2; ACE2; immunity; respiratory tract infections